The modulatory influence of a predictive cue on the auditory steady-state response - Weisz, Nathan; Lecaignard, Francoise; Müller, Nadia; Bertrand, Olivier (Human Brain Mapping, 2012)
Whether attention exerts its impact already on primary sensory levels is still a matter of debate. Particularly in the auditory domain the amount of empirical evidence is scarce. Recently noninvasive and invasive studies have shown attentional modulations of the auditory Steady-State Response (aSSR). This evoked oscillatory brain response is of importance to the issue, because the main generators have been shown to be located in primary auditory cortex. So far, the issue whether the aSSR is sensitive to the predictive value of a cue preceding a target has not been investigated. Participants in the present study had to indicate on which ear the faster amplitude modulated (AM) sound of a compound sound (42 and 19 Hz AM frequencies) was presented. A preceding auditory cue was either informative (75%) or uninformative (50%) with regards to the location of the target. Behaviorally we could confirm that typical attentional modulations of performance were present in case of a preceding informative cue. With regards to the aSSR we found differences between the informative and uninformative condition only when the cue/target combination was presented to the right ear. Source analysis indicated this difference to be generated by a reduced 42 Hz aSSR in right primary auditory cortex. Our and previous data by others show a default tendency of "40 Hz" AM sounds to be processed by the right auditory cortex. We interpret our results as active suppression of this automatic response pattern, when attention needs to be allocated to right ear input. © 2011 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Auditory cortex; Beamforming; MEG; Selective attention